2015
DOI: 10.1111/jdv.13520
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with alopecia areata: a hospital‐based cross‐sectional study

Abstract: Our study demonstrates that AA influences QoL, but to a lesser degree than observed for psoriasis, atopic dermatitis and onychomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 32 publications
4
45
0
1
Order By: Relevance
“…1 The most common hair diseases are alopecia areata (AA) and alopecia androgenetica (AGA). 1 The most common hair diseases are alopecia areata (AA) and alopecia androgenetica (AGA).…”
Section: Introductionmentioning
confidence: 99%
“…1 The most common hair diseases are alopecia areata (AA) and alopecia androgenetica (AGA). 1 The most common hair diseases are alopecia areata (AA) and alopecia androgenetica (AGA).…”
Section: Introductionmentioning
confidence: 99%
“…6,8,9,11,2026 Across all Skindex-29 subscales, QoL for adults with facial PWS (composite score, 24.6) was lower than QoL for persons without skin disease (composite score, 9). Facial PWS was the third-lowest mean Skindex-29 score (composite score and subscore), with the emotion subscore being the most affected (mean, 34.4; SD = 25.8).…”
Section: Resultsmentioning
confidence: 91%
“…68 Although isolated PWS are generally thought to be asymptomatic (i.e., without pruritus, pain, major functional impairment), previous studies have demonstrated adversely impaired QoL in similarly asymptomatic skin conditions, such as vitiligo and alopecia. 911 The distinct appearance of PWS and potential complications might significantly impact a person’s psychosocial development and well-being. 12,13 Furthermore, the face is intimately associated with personal identity and social interactions.…”
mentioning
confidence: 99%
“…Otra herramienta común es el Symptom Check List-90-R (SCL-90-R), un instrumento de cuantificación sintomática que permite medir la intensidad de 90 síntomas psicológicos y psicopatológicos 10 . Los cuestionarios Dermatology Life Quality Index (DLQI), Short Form-36 Health Survey (SF-36) y Skindex-29 fueron desarrollados para evaluar la calidad de vida en los problemas de la piel, pero también se utilizan en la alopecia ante la escasez de escalas específicas en este campo 11 .…”
Section: Epidemiología E Impactounclassified